2015
DOI: 10.1073/pnas.1511810112
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s disease: Neural dysfunction linked to inositol polyphosphate multikinase

Abstract: Huntington's disease (HD) is a progressive neurodegenerative disease caused by a glutamine repeat expansion in mutant huntingtin (mHtt). Despite the known genetic cause of HD, the pathophysiology of this disease remains to be elucidated. Inositol polyphosphate multikinase (IPMK) is an enzyme that displays soluble inositol phosphate kinase activity, lipid kinase activity, and various noncatalytic interactions. We report a severe loss of IPMK in the striatum of HD patients and in several cellular and animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…Expression of IPMK has been shown to be lower in pathological samples from patients with Huntington disease as well as in cellular and animal models of Huntington disease. 29 Phosphatidylinositol kinase activity (one of the enzymatic functions of IPMK) has also been shown to be lower in postmortem tissue from patients with AD. 30 Considered together with our results, these studies suggest an important role for IPMK in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of IPMK has been shown to be lower in pathological samples from patients with Huntington disease as well as in cellular and animal models of Huntington disease. 29 Phosphatidylinositol kinase activity (one of the enzymatic functions of IPMK) has also been shown to be lower in postmortem tissue from patients with AD. 30 Considered together with our results, these studies suggest an important role for IPMK in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…As with Bcl11b IPMK is reduced in HD cell lines and mouse models and indeed it was found in R6/2 HD mouse model that virally transfected intrastriatal IPMK delivery prevents the progression of psychomotor dysfunction and reduces striatal pathology. Similarly Desplats et al found that the deleterious impacts of Huntingtin protein in the Q111 cell line are diminished when Bcl11b is expressed at supranormal levels (Ahmed et al, 2015). Reversing the loss of Bcl11b-IPMK expression is therefore a promising novel therapeutic target in HD.…”
Section: Involvement In Pathologymentioning
confidence: 95%
“…Bc11b is significantly diminished in HD cell lines, mouse models and human CSF and tissue samples. Ahmed et al suggest that the toxic effects of Bcl11b deficiency are mediated by decreases in inositol polyphosphate multikinase (IPMK; Ahmed et al, 2015). IPMK, a kinase and a transcriptional co-activator, is severely diminished in Bcl11b knockout cells lines and is returned to normal levels when Bcl11b is replaced.…”
Section: Involvement In Pathologymentioning
confidence: 99%
“…Examining the adult and aging human as well as rodent brain suggests Bcl11b to be involved in a number of neurodegenerative disorders like Alzheimer's disease (AD) (Desplats et al, 2008;Choi et al, 2018;Dard et al, 2018;Llorens-Martin, 2018), Huntington's disease (HD) (Desplats et al, 2008;Ahmed et al, 2015), schizophrenia (Whitton et al, 2016(Whitton et al, , 2018, and amyotrophic lateral sclerosis (ALS) (Chesi et al, 2013;Lennon et al, 2016). One common feature of neurodegenerative diseases including HD, AD, Parkinson disease as well as ALS, is the loss of synapses (Hong et al, 2016;Bae and Kim, 2017;Sellgren et al, 2019).…”
Section: Bcl11 Transcription Factors and Neurological Disordersmentioning
confidence: 99%